CHURCH, "MINJUNG" AND STATE: THE REVIVAL OF PROTESTANT CHRISTIANITY IN NORTH KOREA - KEUM, Jooseop (Studia Universitatis Babeș-Bolyai Theologia Orthodoxa, 2019)
The issue of church and state takes us to the heart of mission because the Gospel is the good news in every part of human life and society. Throughout the history of the Church in Korea, the issues of church and state, religion and society have been deeply connected to the development of the Korean churches. Indeed, an important factor in Christianity’s success in Korea has been its frequent identification with political movements promoting Korean nationalism, independence, democracy, and Korean reunification. Especially in Northern Korea before the division of the peninsula in 1945, and in North Korea after it, the church-state relationship has been one of the crucial issues determining the fate of the churches. It is the purpose of this article to introduce the revival of Protestant Christianity in North Korea in the Communist context, with special reference to issues of church and state.